Adaptations of animals to extreme climatic conditions (Zoological Records and Reviews, 2024)
Animals occupying thermally extreme environments--polar regions, hyper-arid deserts, hydrothermal vents, andhigh-altitude plateaux--have evolved a diverse suite of morphological, physiological, and behavioural adaptations thatenable survival and reproduction under conditions lethal to most species. This comparative study quantifies key adaptivetraits in 24 vertebrate and invertebrate taxa representing four extreme climate zones: Arctic/Antarctic (n = 6 taxa), hotdesert (n = 6), high altitude (n = 6), and deep-sea hydrothermal vent (n = 6). Trait data were compiled from fieldmeasurements and laboratory experiments conducted across Denmark, France, and partner institutions between 2019and 2023 (n = 847 individual measurements). Thermal tolerance breadth (CTmax - CTmin) ranged from 4.2degC in thestenothermal Antarctic icefish Chionodraco hamatus to 52.8degC in the Saharan silver ant Cataglyphis bombycina, thewidest recorded tolerance in any animal. Basal metabolic rate (BMR) in polar endotherms was 38-67% higher thanpredicted by Kleiber's allometric equation, while desert ectotherms exhibited BMR suppression of 31-54% duringaestivation. Haemoglobin oxygen affinity (P50) in high-altitude taxa was 18-34% lower than sea-level congeners,conferring enhanced oxygen loading at reduced partial pressures. Molecular chaperone (Hsp70) expression levels underheat stress were 4.2-fold higher in desert-adapted taxa than in temperate controls. These findings are synthesised into across-taxa adaptation framework linking environmental extremity index to trait divergence magnitude, providing aquantitative baseline for predicting vulnerability of extreme-climate specialists to ongoing climate change.
Keywords: climate change vulnerability; hydrothermal vent; high altitude; desert ectotherms; polar endotherms; Hsp70; haemoglobin affinity; basal metabolic rate; thermal tolerance; thermal adaptation